Investigating challenges in producing adherent Boron Nitride PVD coatings for tooling and additive manufacturing applications - Cooper, Timothy Paul (2023)
Magnetron Sputtering Physical Vapour Deposition (MS-PVD) is a process capable of depositing thin (< 10 µm) layers of myriad materials onto vacuum stable components. Boron Nitride (BN) is a ceramic with potential for use in surface coating and alloy doping due to its desirable mechanical properties. Multiple issues prevent adoption of BN as a coating material, related to its low deposition rate, low adherence, and the intensive processing required.